2021
DOI: 10.1097/brs.0000000000004070
|View full text |Cite
|
Sign up to set email alerts
|

Combined Motor and Sensory Intraoperative Neuromonitoring for Cervical Spondylotic Myelopathy Surgery Causes Confusion

Abstract: Level-1 diagnostic study.Objective. The purpose of this study was to evaluate the sensitivity and specificity of combined motor and sensory intraoperative neuromonitoring (IONM) for cervical spondylotic myelopathy (CSM). Summary of Background Data. Intraoperative neuromonitoring during spine surgery began with sensory modalities with the goal of reducing neurological complications. Motor monitoring was later added and purported to further increase sensitivity and specificity when used in concert with sensory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…With the deepening of clinical and imaging technology cooperation and the study of many cases, many scholars have found that high signal does not necessarily indicate a poor prognosis. [17,[35][36][37][38][39] It is proposed that patients with high signal after surgery are better than those with low signal or no signal, and some scholars have found that whether there is high signal before surgery is not directly related to the degree of spinal cord compression or the efficacy of surgery. Some cases of hyperintensity can have reversible changes and have a good prognosis [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the deepening of clinical and imaging technology cooperation and the study of many cases, many scholars have found that high signal does not necessarily indicate a poor prognosis. [17,[35][36][37][38][39] It is proposed that patients with high signal after surgery are better than those with low signal or no signal, and some scholars have found that whether there is high signal before surgery is not directly related to the degree of spinal cord compression or the efficacy of surgery. Some cases of hyperintensity can have reversible changes and have a good prognosis [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 – 16 ] In order to solve this problem, some scholars proposed to use somatosensory-evoked potential amplitude and latency to assess patients after spinal cord surgery to a certain extent recovery effect and changes in somatosensory-evoked potential amplitude and incubation period. [ 17 19 ] The main basis for evaluating the effect of surgical treatment is that the amplitude of the evoked potential can determine the number of neurons in response to the stimulus (when the number of neurons in response to the stimulus decreases, the amplitude curve of the evoked potential decreases) and then determine the electrical conductivity of the injured neurons to the evoked potential when the spinal cord is compressed [ 20 – 22 ], which indirectly reflects the number of spinal cord nerve injuries in the patients. The literature shows that the level of SEP amplitude combined with morphological testing can more accurately determine the patient's injury and recovery [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, somatosensory evoked potentials (SSEPs) directly monitor ascending sensory tracts and may be therapeutically useful in combination with TcMEPs, although institutional standard of care may dictate use of monitoring modalities. 33,34 A Delphi consensus report published in 2014 outlines a standardized checklist protocol in response to IONM alarms such as TcMEP changes. 23 The protocol involves alerting the neurophysiologist and surgeon, optimizing hemodynamic parameters and other vital signs, examining the status of anesthetic and paralytic agents, evaluating the surgical field for spinal cord/ nerve root compression, and employing surgical maneuvers to reverse the TcMEP change to baseline values.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, somatosensory evoked potentials (SSEPs) directly monitor ascending sensory tracts and may be therapeutically useful in combination with TcMEPs, although institutional standard of care may dictate use of monitoring modalities. 33,34…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 91 concluded the false-positive rate of their series to be 83%, with a PPV of 17%. Taylor et al 92 evaluated prospective neuromonitoring data of 540 patients with cervical spondylotic myelopathy who underwent anterior or posterior decompressive surgery. The authors reported an IONM alert incidence of 1.3%, noting all were false positives.…”
Section: Challengesmentioning
confidence: 99%